2022
DOI: 10.1038/s41598-022-05449-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistent extreme ultraviolet irradiance in Antarctica despite the ozone recovery onset

Abstract: Attributable to the Montreal Protocol, the most successful environmental treaty ever, human-made ozone-depleting substances are declining and the stratospheric Antarctic ozone layer is recovering. However, the Antarctic ozone hole continues to occur every year, with the severity of ozone loss strongly modulated by meteorological conditions. In late November and early December 2020, we measured at the northern tip of the Antarctic Peninsula the highest ultraviolet (UV) irradiances recorded in the Antarctic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
(79 reference statements)
0
22
0
Order By: Relevance
“…The terrestrial ecosystem in Antarctica is experiencing harsh environments, such as enhanced UV radiation, shortage of available water resources and low temperature [ 28 ]. In the past two decades, due to the destruction of the ozone layer hole, the surface of Antarctica has been continuously exposed to UV-B radiation [ 36 ]. From November to December in 2020, the highest UV irradiance of the Antarctic continent was recorded in the last 20 years at the northern part of the Antarctic Peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…The terrestrial ecosystem in Antarctica is experiencing harsh environments, such as enhanced UV radiation, shortage of available water resources and low temperature [ 28 ]. In the past two decades, due to the destruction of the ozone layer hole, the surface of Antarctica has been continuously exposed to UV-B radiation [ 36 ]. From November to December in 2020, the highest UV irradiance of the Antarctic continent was recorded in the last 20 years at the northern part of the Antarctic Peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…Using observations from satellites between 1978 and 2020, a recent study [ 34 ] compared annual averages of the depth and area of the Antarctic ozone hole for early spring (1 September–15 October) and late spring (16 October–30 November). This analysis is of high relevance for assessing trends in UV radiation over Antarctica because UV radiation is generally much greater later in spring when the Sun is higher in the sky even though TCO is typically much lower earlier in spring.…”
Section: Current and Future Status Of Atmospheric Ozonementioning
confidence: 99%
“…Since the onset of stratospheric ozone depletion, the maximum has shifted to the spring season. Despite this change in time and intensity, previous work showed that actual UV-B levels in the summer season increased by approximately 15% when compared with the same period before the ozone depletion 7,8 . Since the Antarctic troposphere is now exposed to dramatically higher quantities of UV-B radiation, it is no longer in a "natural" state 8,9 .…”
mentioning
confidence: 91%
“…Despite this change in time and intensity, previous work showed that actual UV-B levels in the summer season increased by approximately 15% when compared with the same period before the ozone depletion 7,8 . Since the Antarctic troposphere is now exposed to dramatically higher quantities of UV-B radiation, it is no longer in a "natural" state 8,9 . Among the impacts on the atmospheric chemistry by ozone hole and UV-B incidence, the investigation of sea salt aerosols plays a critical role, as it takes part in radiative processes at the maritime boundary layer 10,11 .…”
mentioning
confidence: 91%